2022
DOI: 10.1002/advs.202200169
|View full text |Cite
|
Sign up to set email alerts
|

SHF Acts as a Novel Tumor Suppressor in Glioblastoma Multiforme by Disrupting STAT3 Dimerization

Abstract: Sustained activation of signal transducer and activator of transcription 3 (STAT3) is a critical contributor in tumorigenesis and chemoresistance, thus making it an attractive cancer therapeutic target. Here, SH2 domain‐containing adapter protein F (SHF) is identified as a tumor suppressor in glioblastoma Multiforme (GBM) and its negative regulation of STAT3 activity is characterized. Mechanically, SHF selectively binds and inhibits acetylated STAT3 dimerization without affecting STAT3 phosphorylation or acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…STAT3 has been shown to have the potential as a therapeutic target for glioma [12]. The continuous activation of STAT3 in glioma cell can promote proliferation and migration and inhibit apoptosis [13,14]. This study found that bergaptol treatment significantly reduced p-STAT3 phosphorylation ratio and Bcl-2 protein levels and increased Caspase-3 expression dose dependently (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…STAT3 has been shown to have the potential as a therapeutic target for glioma [12]. The continuous activation of STAT3 in glioma cell can promote proliferation and migration and inhibit apoptosis [13,14]. This study found that bergaptol treatment significantly reduced p-STAT3 phosphorylation ratio and Bcl-2 protein levels and increased Caspase-3 expression dose dependently (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…In a bioinformatics analysis, QI et al,(2023) [98] reported that BHLHE40 was overexpressed in 7 of 33 tumor tissues, including GBM tissues, and predicted worse OS in both high-and low-grade gliomas. Among the genes downregulated with MUC1 expression, SHF plays a tumor suppressor role in GBM by negatively regulating signal transducer and activator of transcription 3 (STAT3) activity, and its low expression predicts worse OS [99]. Additionally, low KLHL23 and MATR3 expression is also associated with poor survival in patients with different tumors [100][101][102][103].…”
Section: Discussionmentioning
confidence: 99%
“…The IHC procedure was performed as described in our previous studies. 56 , 57 The slides were incubated with primary antibodies. Cell nuclei were counterstained lightly with crystal violet.…”
Section: Methodsmentioning
confidence: 99%
“…3D-Spheroid formation and growth assay was performed as described previously. 56 , 57 Briefly, the detached cells were resuspended in GBO medium with a minor modification (without insulin) according to a previously published report. 61 Cells were seeded in the non-adherent 96-well plate (Corning, NY) at 400 cells/well.…”
Section: Methodsmentioning
confidence: 99%